The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.30684/etj.v38i7a.469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polarity of Electro Discharge Machine (EDM) on Surface Roughness (SR) and Metal Removal Rate (MRR) of Low Carbon Steel

Abstract: Electro discharge machining (EDM) is one of a thermal process that is used for remove of metal from the workpiece by spark erosion. The work of this machine depends on multiple variables. One of the more influential variants on this machine is the change of polarity and the use of this variable is not wide and the research depends on the polarity of the machinist. Essentially, the polarity of the tool (electrode) is positive and the workpiece is negative, this polarity can be reversed. This paper  focuses on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Schulze HP et al [86] discussed polarity change in electric discharge machining and reported reverse polarity has a greater influence on tool wear rate. Taqi S et al [87] experimentally investigated about the influence of polarities on material removal rate. Reverse polarity is suggested to have better removal rate from the tool electrode and directly influences the coating thickness.…”
Section: Electrode Polaritymentioning
confidence: 99%
“…Schulze HP et al [86] discussed polarity change in electric discharge machining and reported reverse polarity has a greater influence on tool wear rate. Taqi S et al [87] experimentally investigated about the influence of polarities on material removal rate. Reverse polarity is suggested to have better removal rate from the tool electrode and directly influences the coating thickness.…”
Section: Electrode Polaritymentioning
confidence: 99%
“…The mechanism of removing the metals by generating a spark electrical between the poles as the (tool) electrode and the work piece, where the materials of both of the electrode and the work piece must be an electrically conductive for performed the operation [3].The behaviors of the material are different due to the differences made during the manufacture of each of the electrodes as well as for the piece of work in EDM and because each material has a different composition so it is necessary to know the properties of these materials to be customized on any electrode material that gives the highest materials removal rate and the best surface finish [4]. So in this paper was proposed to study the effected of various electrode materials and the input parameters are the currents and the pulses in the time on the output result are the materials removals rates (MRR) and the surface roughness (SR) [5]. Figure 1 shows the schematic diagram of the EDM system [6].…”
Section: Introductionmentioning
confidence: 99%